Microbial therapeutic interventions. Issue 6 (December 2016) - Grady, Nicole G.; Petrof, Elaine O.; Claud, Erika C.
Summary: The microbiome comprises all the microbes living in and on the human body. Human cells are greatly outnumbered by bacterial cells; thus human health depends on the health of the microbial ecosystem. For the immature preterm infant, the microbiome also influences intestinal and immune system development. This has implications for short term morbidities such as neonatal necrotizing enterocolitis and sepsis, but also long term health outcomes. Optimization of the preterm infant microbiome is a growing topic of interest. The microbial world is not one of good versus evil, but rather one of community; thus optimization includes not only minimizing pathogens, but also enhancing beneficial organisms. Options for optimization include judicious antibiotic use, administration of supplements such as prebiotics or probiotics, and transfaunation procedures such as fecal microbial transplant or microbial ecosystem therapeutics. Potential for benefit as well as risk for each of these options will be discussed.